HUBUNGAN KONSUMSI SAYURAN HIJAU DENGAN ANEMIA PADA IBU HAMIL DI PUSKESMAS REMBANG KABUPATEN PURBALINGGA - Rahayu, Lina Dwi Puji; Suryani, Evi Sri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Anemia in pregnancy adversely impact both the pregnant mother, childbirth or in the postpartum period and beyond. Therefore, prevention efforts are needed. One of the prevention of anemia in pregnant women is consumption of green vegetables with proper portions each day. Objectives of research to identify the causes of some of the determinants of anemia in pregnant women in health centers Apex Purbalingga Year 2013. This research is a descriptive study with cross sectional analytic. The study sample of 50 pregnant women in the third trimester Apex Purbalingga Health Center in 2013. Univariate analysis using frequency distribution and bivariate analysis using chi square test. Results of research show that consumption green vegetable consumption among pregnant women at no more than good enough category (46.0%). Most pregnant women do not have anemia that is 34 people (68.0%). There is a relationship consumption of green vegetables with the incidence of anemia in pregnant women (p = 0.004). Conclusion of research conducted that there is a relationship between the consumption of green vegetable consumption with the incidence of anemia in pregnant women. Keywords: Pregnant women, green vegetables, anemia